2020
DOI: 10.22541/au.159056294.45813944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small differences in root distributions allow resource niche partitioning

Abstract: 1. Deep roots have long been thought to allow trees to coexist with shallow-rooted grasses. Due to the difficulties of working belowground, data demonstrating water uptake and niche partitioning are uncommon. 2. We describe tree and grass root distributions using a depth-specific tracer experiment in a subtropical savanna, Kruger National Park, South Africa. The depthspecific tracer experiment was conducted three times during each of two growing seasons. These point-in-time measurements (i.e., tracer-defined r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In agreement with this hypothesis, some recent studies (e.g. Kulmatiski et al, 2017Kulmatiski et al, , 2020 comparing trees and grasses have indeed shown that nitrogen and water uptake may in part be spatially decoupled in trees, with a preference for shallow nutrient-rich layers for nitrogen uptake.…”
Section: Linking Water-use Strategy the Leaf Economic Spectrum And Sp...supporting
confidence: 54%
“…In agreement with this hypothesis, some recent studies (e.g. Kulmatiski et al, 2017Kulmatiski et al, , 2020 comparing trees and grasses have indeed shown that nitrogen and water uptake may in part be spatially decoupled in trees, with a preference for shallow nutrient-rich layers for nitrogen uptake.…”
Section: Linking Water-use Strategy the Leaf Economic Spectrum And Sp...supporting
confidence: 54%
“…This result is supported by prior evidence for phylogenetic signals in root traits that may carry implications for RWU (Comas & Eissenstat, 2009; McCormack et al., 2020; Valverde‐Barrantes et al., 2017). Some ecosystems show evidence of seasonal oscillations between niche segregation and direct competition driven by seasonal soil water limitation (Andrews et al., 2012; De Deurwaerder et al., 2018; Kulmatiski et al., 2020; McCormack et al., 2020; Rodríguez‐Robles et al., 2020), suggesting higher‐order interactions between the phylogenetic, niche, and locality hypotheses. In a mixed species forests, co‐occurring trees may rely on similar water sources during dry days, but exhibit divergent RWU depths in response to recent precipitation (Grossiord et al., 2017; Liu et al., 2019; Volkmann et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Still, at a finer scale, trade-offs can exist among specializations for N, P, or water acquisition. For instance, deeper rooting may favor water acquisition, whereas shallower roots should enhance N acquisition (Kulmatiski et al, 2020). Moreover, mycorrhizal status may reflect a specialty for P versus N acquisition (Read & Perez-Moreno, 2003).…”
Section: Discussionmentioning
confidence: 99%